PENGARUH SELF-EFFICACY, PERCEIVED ORGANIZATIONAL SUPPORT DAN QUALITY OF WORK LIFE TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN SITUBONDO - Niesya Monica Junearta; Yudha Praja; Ediyanto Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
Changes in the work environment and increasingly complex job demands require organizations to pay attention to employee psychological factors, organizational support, and quality of work life in order to create optimal employee satisfaction and performance. The purpose of this study is to analyze and test the effect of Self-Efficacy, Perceived Organizational Support, and Quality of Work Life on Employee Performance through Job Satisfaction in the General Section of the Situbondo Regency Regional Secretariat. This research is an explanatory study. The populations in this study were 63 non-PNS ASN employees in the General Section of the Situbondo Regency Regional Secretariat. The sampling technique was determined using a non-probability sampling technique through a saturated sampling method. The data analysis and hypothesis testing in this study used Structural Equation Model-Partial Least Square (PLS-SEM) with SmartPLS 3.0 application. The results of the direct effect hypothesis test show that Self-Efficacy has a negative and insignificant effect on Job Satisfaction, Perceived Organizational Support has a positive but insignificant effect on Job Satisfaction, Quality of Work Life has a positive and significant effect on Job Satisfaction, Self-Efficacy has a positive but insignificant effect on Employee Performance, Perceived Organizational Support has a negative and insignificant effect on Employee Performance, Quality of Work Life has a positive but insignificant effect on Employee Performance, and Job Satisfaction has a positive and significant effect on Employee Performance. The results of the indirect effect hypothesis test show that Self-Efficacy has a negative and insignificant effect on Employee Performance through Job Satisfaction, Perceived Organizational Support has a positive but insignificant effect on Employee Performance through Job Satisfaction, while Quality of Work Life has a positive and significant effect on Employee Performance through Job Satisfaction.